Relationship between Absolute Lymphocyte Count and Ascites in Patients with Liver Cirrhosis - Riyadi, Nathasya Rizkyana; Carmelita, Austin Bertilova; Sasmithae, Lia; Kahanjak, Donna Novina; Putra S, Ravenalla Abdurrahman Al Hakim Sampurna (The Indonesian Society for Digestive Endoscopy, 2023)
Background: Cirrhosis is the final stage of liver disease characterized by fibrosis and irreversible nodule formation due to chronic inflammation. The most common liver cirrhosis complication is ascites, where pathological fluid accumulates in the peritoneal cavity. In cirrhosis, lymphocytes infiltrate the liver and contribute to stellate cell activation, differentiation, and the fibrogenic response. Many recent studies have not studied a relationship between the absolute lymphocyte count and ascites in liver cirrhosis. Therefore, it is important to investigate the relationship between lymphocytes and ascites in liver cirrhosis.Method: This is an observational study with a cross-sectional design study. Held in August–October 2022 at Dr. Doris Sylvanus Hospital's Medical Record Installation. 64 samples were selected based on inclusion and exclusion criteria. Meanwhile, absolute lymphocyte count were measured from the patient's blood tests or by calculation. Ascites were diagnosed by physical examination and radiology. The relationship between absolute lymphocyte count and ascites was analyzed using the chi-square test, with the results considered statistically significant when the p-value 0.05.Result: The medical records from April 2019 to April 2022, there were 64 samples, of which 15 and 49 were without and with ascites. Based on the chi-square test results, there was a significant relationship between absolute lymphocyte count and the incidence of ascites, with p = 0.02.Conclusion: This study concluded that there is a relationship between absolute lymphocyte count and ascites in patients with liver cirrhosis, where absolute lymphocyte count tends to decrease.